An Arduino-based voice-recognition elevator for special purposes - Hassan Falah Fakhruldeen; Azal Alaa Meri; Ali Hameed Sa'id; Alaa Naeem Makttoof; Musafer Awad Kadhim; Heba Abdul-Jaleel Al-Asady (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
This paper presents the design and implementation of five floors electrical elevator system that utilizes voice recognition technology, specifically using an Arduino microcontroller, for special applications. The purpose of this project is to provide a convenient and accessible means of transportation for individuals with disabilities, specifically those who may have difficulty using traditional elevators due to physical limitations or mobility issues. The system consists of an Arduino microcontroller, a voice recognition module, a motor driver, and an elevator car with a lift mechanism. The microcontroller receives voice commands from the user and processes them to determine the desired floor. The motor driver then activates the lift mechanism to move the car to the desired floor. The system was tested and found to be reliable and efficient in transporting individuals to their desired floor. It has the potential to greatly improve the accessibility and convenience of buildings for individuals with disabilities.